Onset of tearing modes in plasma termination on JET: the role of temperature hollowing and edge cooling. (12th March 2021) - Pucella, G.; Buratti, P.; Giovannozzi, E.; Alessi, E.; Auriemma, F.; Brunetti, D.; Ferreira, D.R.; Baruzzo, M.; Frigione, D.; Garzotti, L.; Joffrin, E.; Lerche, E.; et al.
Abstract: In this work the onset of tearing modes in the termination phase of plasma pulses on JET is investigated. It is shown that the broadening or the shrinking of the current density profile, as a consequence of a core hollowing or an edge cooling of the electron temperature profile, strongly increases the probability of destabilizing a 2/1 tearing mode also in absence of an external trigger (e.g. a sawtooth crash). Two parameters are defined to highlight changes in the shape of the temperature profile that can lead to MHD instabilities and an empirical stability diagram is introduced into the space of the two new parameters. A large data-set of pulses carried out in the high-current scenario at JET with ITER-like wall is analyzed and criteria for the development of disruption alerts based on the two risk indicators for MHD instabilities are discussed, taking into account the different dynamics of the observed phenomena leading to the onset of 2/1 tearing modes.